Myositis Ossificans in Sport: A Review. Issue 9 (September 2018) - Devilbiss, Zachary; Hess, Matthew; Ho, Garry W.K.
Abstract : Myositis ossificans is a benign, solitary, frequently self-limiting, ossifying soft-tissue mass encountered often in the active sporting population. Typically occurring within skeletal muscle — most often the brachialis, quadriceps and adductor muscle groups — lesions may arise with or without a traumatic history. The exact pathophysiology of these ossifying lesions is still poorly understood. Patients present with localized pain and swelling with loss of range of motion. Plain radiographs may not be able to detect early lesions, which allows for an expanded role of ultrasonography as an early screening modality, despite magnetic resonance imaging remaining the gold standard for imaging of soft tissue masses. Conservative treatment is implemented for most patients with excellent outcomes, with surgical excision being an option for persistent symptoms or progressive disease. Typically, athletes are able to progress to light activity at 2 to 3 months, full activity by 6 months, and back to their preinjury level by 1 year.